Management of Village Funds to Improve Development in Galung Village, Barru Regency - Illiyyiin Nasution; Sri Astuty; Citra Ayni Kamaruddin; Irwandi; Diah Retno Dwi Hastuti (Journal of Law and Economics, 2025)
This study examines the effectiveness of village fund management in enhancing development, analyzes the impact of village funds on development improvement, and identifies supporting and inhibiting factors for village fund realization in Galung Village, Barru Regency. The research employs a qualitative descriptive method with a case study approach. Data collection utilized primary and secondary sources, including the Galung Village Budget Realization Report and interviews with key informants. Data analysis combined effectiveness ratio analysis and qualitative data analysis through data organization and coding, theme and pattern identification, data interpretation, narrative compilation, verification, triangulation, and conclusion drawing. The findings reveal that village fund management effectiveness in Galung Village, Barru Regency during 2019-2023 achieved an effective category with 100% realization rate annually. Village funds positively impacted development through infrastructure improvements that enhanced accessibility, facility utilization, and community quality of life. Supporting factors for village fund realization include clear government policies and robust technology information systems. Meanwhile, inhibiting factors encompass limited human resource capacity, adverse weather conditions, and insufficient community participation.